AMBIVALENSI TEKNOLOGI KOMUNIKASI DALAM FENOMENA GLOBAL VILLAGE VS GLOBAL PILLAGE - Vannyora Okditazeini (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
This paper elaborates on how the development of communication media enables us to communicate with anyone, anywhere. "Everywhere" becomes "nowhere," a concept commonly referred to as globalization. However, like a double-edged sword, globalization, as a manifestation of the global village, has given rise to the sensation of being 'plundered,' commonly known as global pillage. This paper is a conceptual piece that adapts the meta-synthesis methods of Francis and Baldesari by incorporating the concepts of the global village and global pillage put forth by Marshall McLuhan. The results reveal that the phenomenon of globalization, as a synthesis of the global village and global pillage, has brought about several key issues that require critique and should not be taken for granted. The Global village undeniably offers numerous advantages, including: (1) reducing the constraints of time and space, (2) enhancing communication and information dissemination, (3) self-improvement opportunities, (4) transforming audiences from passive consumers to active participants in media consumption, (5) fostering dynamic relationships between the local and the global, among others. On the other hand, the negative consequences emerge as the phenomenon of global pillage, including: (1) increased unemployment due to the inability to compete with global resources, (2) declining per capita income, (3) widespread layoffs, (4) reduced public services, (5) a deteriorating work environment, (6) the demise of small businesses, and (7) the emergence of dialectical relationships between democracy and globalization.